2018
DOI: 10.1155/2018/9796784
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Low‐Power Design of a Multicell Multiuser Massive MIMO System at 3.7 GHz for 5G Wireless Networks

Abstract: Massive MIMO techniques are expected to deliver significant performance gains for the future wireless communication networks by improving the spectral and the energy efficiencies. In this paper, we propose a method to optimize the positions, the coverage, and the energy consumption of the massive MIMO base stations within a suburban area in Ghent, Belgium, while meeting the low power requirements. The results reveal that massive MIMO provides better performances for the crowded scenario where users’ mobility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A multi-cell massive MIMO network system consisting of L cells, each containing one BS with multiple antenna elements is considered in this study, as shown in Figure 1. This model is similar to the ones proposed in [18][19][20] in which each BS communicates coherently with the single-antenna users using the time division duplex (TDD) operating mode. This latter is considered to obtain the downlink signaling informations from the uplink pilots thanks to the channel reciprocity property it relies on.…”
Section: System Modelmentioning
confidence: 92%
See 3 more Smart Citations
“…A multi-cell massive MIMO network system consisting of L cells, each containing one BS with multiple antenna elements is considered in this study, as shown in Figure 1. This model is similar to the ones proposed in [18][19][20] in which each BS communicates coherently with the single-antenna users using the time division duplex (TDD) operating mode. This latter is considered to obtain the downlink signaling informations from the uplink pilots thanks to the channel reciprocity property it relies on.…”
Section: System Modelmentioning
confidence: 92%
“…In this paper, we proceed with the simulations of the optimal massive MIMO 5G networks to investigate the scenarios described above. We apply a capacity-based network deployment tool proposed in [19], in which the optimization algorithm in Figure 3 is implemented. The optimization algorithm of the tool is based on the BS-user association principle and optimizes the initial set of the base stations deployed in the area of interest while meeting the following optimization constraints: (i) the obtained network must have the least possible power consumption, (ii) the DL and UL EMF exposure resulting from the obtained 5G networks must be minimal, (iii) the network must respond to the instantaneous bit rates (voice and data) requested by the users and (iv) must provide a coverage for at least 95% of the users.…”
Section: Optimization Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al [14] have proposed a graph coloring based pilot assignment scheme by utilizing the large-scale coefficients between the access points and user terminals which is capable of reducing the effect of pilot contamination. A method for optimization of coverage, positions, and energy consumption of m-MIMO for low power requirements has been proposed [15]. Al-hubaishi et al [16] have proposed a partial pilot allocation scheme capable of increasing the uplink rate of users in a multi-cell scenario by exploiting the large-scale characteristics of fading channel so that users having poor channel conditions are saved from harsh interference.…”
Section: Introductionmentioning
confidence: 99%